ESP under Hypnosis: The Role of Induction Instructions and Personality Characteristics. - Tressoldi, Patrizio; Del Prete, Guido (Journal of Parapsychology)
In the present study, we compared directly the efficacy of two types of hypnotic induction instructions on a forced-choice clairvoyance task in a sample of participants selected for their medium to high absorption or transliminality scores. The first kind of instructions (ESP) emphasized the capacity to visualize a remote picture, freeing the mind from any thinking activity. The second kind of instructions, the out-of-body experience (OBE), emphasized leaving the body and allowing the mind to go where the target was presented. The two instructions were applied in a within-subject design to control individual differences better. In the 2 sessions of 10 trials each, the mean hit scores were: first session: M = 3.33 (SD = .65); second session: M = 2.41 (SD = .79). The mean hit score of the first session was well above MCE, π = .60; CI: .28-.91; contrast: Δπ = .10. No substantial differences were obtained with the two kinds of instructions. These data replicate the findings obtained by Del Prete and Tressoldi (2005), supporting the hypothesis that a combination of hypnosis and special induction instructions tailored for the ESP task facilitate the performance in participants with medium to high absorption or transliminality scores. Reprinted by permission of the publisher.